2012
DOI: 10.1182/blood-2011-12-399063
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic ATP synthase facilitates transfer of HIV-1 from antigen-presenting cells to CD4+ target cells

Abstract: Antigen-presenting cells (APCs) act as vehicles that transfer HIV to their target CD4+ cells through an intercellular junction, termed the virologic synapse. The molecules that are involved in this process remain largely unidentified. In this study, we used photoaffinity labeling and a proteomic approach to identify new proteins that facilitate HIV-1 transfer. We identified ectopic mitochondrial ATP synthase as a factor that mediates HIV-1 transfer between APCs and CD4+ target cells. Monoclonal antibodies agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…6C and D). The ATPase activity of ATP5B was recently shown to be an important factor in influenza A virus release and human immunodeficiency virus 1 (HIV-1) cell-to-cell transfer (70,71). Our findings are consistent with a role for ATP5B in the energetics of virus release and suggest that this protein might be important for the release of a diverse range of viruses.…”
Section: Discussionsupporting
confidence: 85%
“…6C and D). The ATPase activity of ATP5B was recently shown to be an important factor in influenza A virus release and human immunodeficiency virus 1 (HIV-1) cell-to-cell transfer (70,71). Our findings are consistent with a role for ATP5B in the energetics of virus release and suggest that this protein might be important for the release of a diverse range of viruses.…”
Section: Discussionsupporting
confidence: 85%
“…Just as ectopic ATP synthase has the ability to bind to many different ligands (apolipoprotein A-I, angiostatin, β amyloid oligomers, etc.) (22 , 23 , 31 , 32) and to transfer HIV-1 from antigen-presenting cells to CD4 + cells (33) , the sarcolemmal OXPHOS complexes may have as yet unknown non-canonical functions. Thus, a direction for future research on the sarcolemmal OXPHOS proteins is to identify their novel non-canonical functions.…”
Section: Discussionmentioning
confidence: 99%
“…Another drug, Bz-423 that induces apoptosis in lymphoid cells, has been found to inhibit the mitochondrial ATP synthase [ 13 ]. Also, it is been shown that ectopic ATP synthase may be a suitable molecular target for inhibiting HIV-1 proliferation in vivo [ 14 ].…”
Section: Introductionmentioning
confidence: 99%